2022
DOI: 10.3389/fsurg.2022.850662
|View full text |Cite
|
Sign up to set email alerts
|

Explore the Application Value of Prospective Monitoring Model in the Nursing Management of Breast Cancer Patients During Perioperative Period

Abstract: PurposeTo explore the application value of prospective monitoring model in the nursing management of breast cancer patients during perioperative period.Methods300 perioperative breast cancer patients admitted to our hospital from January to August 2021 were randomly divided into the control group (n = 150) and the model group (n = 150). Both groups used routine nursing management, and the model group added nursing management based on a prospective monitoring model. The quality of surgical nursing, circumferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
2
2
0
4
Order By: Relevance
“…Zhang and Zhou (46) showed that DASH presents a negative mean correlation with fatigue levels (r= -0.564; p < 0.005). These results are in line with our results, as well as the study by Zhang and Zhou (2022), DASH presented in our study an inverse correlation with fatigue levels (r= -0.435; p = 0.0005), especially in the domains related to physical wellbeing (r= -0.480; p = 0.0000), the scales of symptoms related to breast cancer (r= -0.345; p = 0.0004) (47).…”
Section: Discussionsupporting
confidence: 93%
“…Zhang and Zhou (46) showed that DASH presents a negative mean correlation with fatigue levels (r= -0.564; p < 0.005). These results are in line with our results, as well as the study by Zhang and Zhou (2022), DASH presented in our study an inverse correlation with fatigue levels (r= -0.435; p = 0.0005), especially in the domains related to physical wellbeing (r= -0.480; p = 0.0000), the scales of symptoms related to breast cancer (r= -0.345; p = 0.0004) (47).…”
Section: Discussionsupporting
confidence: 93%
“…Zhang et al randomly divided 300 perioperative breast cancer patients into a control group (underwent routine care) and an intervention group (comprised of instructions for patients to learn about damage recognition before surgery, self‐monitoring, self‐management, and health promotion). Their result showed that 3 months after surgery, the total DASH scores of the two groups were higher than those before surgery and the scores of the intervention group and the control group were statistically different, which was similar to the results of this study 35 . Since the intervention programs in this study included functional exercise and nurse‐led activity programs, and the DASH scores of both groups were p < 0.05 at the two evaluations, these findings showed that the implemented prevention program could significantly improve upper limb dysfunction in breast cancer patients after surgery.…”
Section: Discussionsupporting
confidence: 86%
“…Their result showed that 3 months after surgery, the total DASH scores of the two groups were higher than those before surgery and the scores of the intervention group and the control group were statistically different, which was similar to the results of this study. 35 Since the intervention programs in this study included functional exercise and nurse-led activity programs, and the DASH scores of both groups were p < 0.05 at the two evaluations, these findings showed that the implemented prevention program could significantly improve upper limb dysfunction in breast cancer patients after surgery.…”
Section: Characteristicsmentioning
confidence: 63%
“…Edema/inchaço no braço Aydin A, Gursoy A (17) Swenson KK, Nissen MJ, Leach JW, Post-White J (20) Ridner SH, Dietrich MS, Kidd N (22) Shallwani SM, Towers A (26) Jeffs E, Wiseman T (29) Armer et al (32) Ammitzbøll et al (33) Temur K, Kapucu S (34) Ridner et al (35) Maree JE, Beckmann D (52) Deveci Z, Karaywurt O, Bilik O, Eyigör S (54) 11 (25,6) Sensação de peso no braço Assis MR, Maraglia PH, Brandão MAG, Peixoto MAP (24) ; Jeffs E, Wiseman T (29) Armer et al (32) Ammitzbøll et al (33) Cansız G, Arıkan Dönmez A, Kapucu S, Borman P (40) Deveci Z, Karaywurt O, Bilik O, Eyigör S (54) (14,0) Dor Jeffs E, Wiseman T (29) Ammitzbøll et al (33) Cansız G, Arıkan Dönmez A, Kapucu S, Borman P (40) Maree JE, Beckmann D (52) Deveci Z, Karaywurt O, Bilik O, Eyigör S (54) (11,6)…”
Section: Atributos Definidoresmentioning
confidence: 99%
“…(1)(2)(3) O recorte do estudo em mulheres com linfedema sobreviventes ao CA de mama foi justificado porque esta sequela é uma condição crônica que afeta continuamente a vida dessas mulheres, sendo objeto de planejamento do autocuidado nas etapas que envolvem a enfermagem, com relevância para a prática clínica. (4)(5)(6)(7) "Autogestão ineficaz do linfedema" é um diagnóstico de enfermagem definido pela NANDA International 2021-2023 (NANDA-I ® ) como: "manejo insatisfatório de sintomas e regime de tratamento, com consequências físicas, psicossociais e espirituais, incluindo mudança nos estilos de vida inerentes, levando a viver com edema relacionado a obstrução ou distúrbio de linfonodos ou vasos linfáticos". O diagnóstico acima foi aprovado (2020) e incluído na NANDA-I ® , no domínio atividade/ repouso, com nível de evidência 2.1 referente ao desenvolvimento do arcabouço conceitual que sustentará as interpretações dos elementos constitutivos do diagnóstico de enfermagem (DE).…”
Section: Introductionunclassified